Synthesis of l‐threitol‐based crown ethers and their application as enantioselective phase transfer catalyst in Michael additions. Issue 6 (21st April 2017) - Rapi, Zsolt; Nemcsok, Tamás; Pálvölgyi, Ádám; Keglevich, György; Grün, Alajos; Bakó, Péter
Abstract: A few newl ‐threitol‐based lariat ethers incorporating a monoaza‐15‐crown‐5 unit were synthesized starting from diethyll ‐tartrate. These macrocycles were used as phase transfer catalysts in asymmetric Michael addition reactions under mild conditions to afford the adducts in a few cases in good to excellent enantioselectivities. The addition of 2‐nitropropane to trans ‐chalcone, and the reaction of diethyl acetamidomalonate with β‐nitrostyrene resulted in the chiral Michael adducts in good enantioselectivities (90% and 95%, respectively). The substituents of chalcone had a significant impact on the yield and enantioselectivity in the reaction of diethyl acetoxymalonate. The highest enantiomeric excess ( ee ) values (99% ee ) were measured in the case of 4‐chloro‐ and 4‐methoxychalcone. The phase transfer catalyzed cyclopropanation reaction of chalcone and benzylidene‐malononitriles using diethyl bromomalonate as the nucleophile (MIRC reaction) was also developed. The corresponding chiral cyclopropane diesters were obtained in moderate to good (up to 99%) enantioselectivities in the presence of the threitol‐based crown ethers. Abstract :